ICTs for improving patients rehabilitation research techniques : third International Workshop, REHAB 2015, Lisbon, Portugal, October 1-2, 2015, Revised selected papers /: third International Workshop, REHAB 2015, Lisbon, Portugal, October 1-2, 2015, Revised selected papers. (2017) - Unknown
No abstract available